Design Of A Mobile-Based Geographic Information System Application For The Secretariat Of The Dprd Province Of North Sumatra - Aldy Alfiansyah; Prayuda, Jaka (Journal of Information Systems and Technology Research, 2022)
The North Sumatra DPRD Secretariat already has an official website containing data and information, namely http://dprd-sumutprov.go.id. However, because this system is based on a website, and the location feature is not available, users will not get information about various DPRDs in North Sumatra along with finding locations and routes to the location accurately. The mobile-based Geographic Information System (GIS) for the North Sumatra DPRD Secretariat is a mobile-based GIS application using Fire Goggle Maps that integrates the Global Positioning System (GPS), either via Android or iOS which is directly connected to Google maps which can be accessed via the internet. The purpose of this system was built for the public to get information about the various locations and routes of DPRD in North Sumatra easily and simply because it can be operated wherever and whenever the user is. Users of this system will be taken to the main page which directs the user to login first so that the user can login directly using a google account or create an account. The purpose of creating a user account is to obtain more accurate mapping information when a user searches for the location of the North Sumatra DPRD, Regency/City DPRD, and City. Applications made can present information based on the selection of each type and provide the closest view of the user's position. The application was made to have an impact on the progress of the North Sumatra Regional House of Representatives Secretariat in technology development.